The Influence of Digital Entrepreneurial Orientation on the Performance of MSMEs in Medan City - Meylida Girsang; Khansa khalishah; Erikson Damanik; Cindy Tri Ananta (Jurnal Ilmiah Accusi, 2025)
This research investigates how Digital Entrepreneurial Orientation (DEO) influences the performance of Micro, Small, and Medium Enterprises (MSMEs) in Medan City through digital capability mechanisms. Drawing upon Resource-Based View theory, Dynamic Capability theory, and Technology-Organization-Environment framework, this study examines how digital entrepreneurial practices create value through enhanced operational efficiency, market reach expansion, and innovation capabilities among MSMEs. Using Structural Equation Modeling with Partial Least Squares (PLS-SEM) analysis on 185 MSMEs in Medan (2023-2024), the research demonstrates that DEO significantly enhances digital capabilities (β = 0.712, p < 0.001) and positively influences MSME performance (β = 0.628, p < 0.001). Digital capabilities substantially mediate the relationship between DEO and MSME performance (indirect effect = 0.487, p < 0.001, VAF = 43.7%). The model explains 68.4% of digital capability variance and 61.9% of MSME performance variance. This study provides comprehensive empirical evidence of how digital entrepreneurial mindset transforms MSME competitiveness and sustainability in emerging market contexts, particularly in post-pandemic digital economy environments